Impact of a short, culturally relevant training course on cancer knowledge and confidence in Western Australia's Aboriginal Health Professionals - Croager, E.; Eades, T.; Pratt, I.; Slevin, Terry (Wiley-Blackwell Publishing Asia, 2010)
Objective: To develop, deliver and evaluate a cancer education course for Indigenous Health Professionals. Method: The cancer education course combines expert presentations, interactive sessions and visits to local cancer treatment centres. Three four-day courses have been run, in both metropolitan and regional Western Australia (WA). Cancer knowledge and confidence were measured at baseline, course completion and at follow-up (six to eight months). Data were analysed within subject. Results: Thirty-five Aboriginal Health Professionals have completed the program, most from rural or remote WA. All confidence items significantly improved at course completion (p<0.005), but improvements for only two items, ‘I know what cancer is’ and ‘I can describe the different common cancers’, were sustained at follow-up (p<0.05). Knowledge of treatment (p<0.05), screening (p<0.05) and the most common cancers in women (p<0.005) were significantly greater after course completion, but increased knowledge was not sustained at follow-up.Conclusion: Demand for places suggests that Aboriginal Health Professionals are interested in developing knowledge, skills and confidence in cancer control. Attendance increased understanding of cancer and improved cancer knowledge however this was not maintained. Implications: A short, culturally relevant training course increases cancer knowledge and confidence, however, ongoing education is needed to maintain this.